(x-3)(x-4)-(x+4)=0

Simple and best practice solution for (x-3)(x-4)-(x+4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-3)(x-4)-(x+4)=0 equation:


Simplifying
(x + -3)(x + -4) + -1(x + 4) = 0

Reorder the terms:
(-3 + x)(x + -4) + -1(x + 4) = 0

Reorder the terms:
(-3 + x)(-4 + x) + -1(x + 4) = 0

Multiply (-3 + x) * (-4 + x)
(-3(-4 + x) + x(-4 + x)) + -1(x + 4) = 0
((-4 * -3 + x * -3) + x(-4 + x)) + -1(x + 4) = 0
((12 + -3x) + x(-4 + x)) + -1(x + 4) = 0
(12 + -3x + (-4 * x + x * x)) + -1(x + 4) = 0
(12 + -3x + (-4x + x2)) + -1(x + 4) = 0

Combine like terms: -3x + -4x = -7x
(12 + -7x + x2) + -1(x + 4) = 0

Reorder the terms:
12 + -7x + x2 + -1(4 + x) = 0
12 + -7x + x2 + (4 * -1 + x * -1) = 0
12 + -7x + x2 + (-4 + -1x) = 0

Reorder the terms:
12 + -4 + -7x + -1x + x2 = 0

Combine like terms: 12 + -4 = 8
8 + -7x + -1x + x2 = 0

Combine like terms: -7x + -1x = -8x
8 + -8x + x2 = 0

Solving
8 + -8x + x2 = 0

Solving for variable 'x'.

Begin completing the square.

Move the constant term to the right:

Add '-8' to each side of the equation.
8 + -8x + -8 + x2 = 0 + -8

Reorder the terms:
8 + -8 + -8x + x2 = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -8x + x2 = 0 + -8
-8x + x2 = 0 + -8

Combine like terms: 0 + -8 = -8
-8x + x2 = -8

The x term is -8x.  Take half its coefficient (-4).
Square it (16) and add it to both sides.

Add '16' to each side of the equation.
-8x + 16 + x2 = -8 + 16

Reorder the terms:
16 + -8x + x2 = -8 + 16

Combine like terms: -8 + 16 = 8
16 + -8x + x2 = 8

Factor a perfect square on the left side:
(x + -4)(x + -4) = 8

Calculate the square root of the right side: 2.828427125

Break this problem into two subproblems by setting 
(x + -4) equal to 2.828427125 and -2.828427125.

Subproblem 1

x + -4 = 2.828427125 Simplifying x + -4 = 2.828427125 Reorder the terms: -4 + x = 2.828427125 Solving -4 + x = 2.828427125 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = 2.828427125 + 4 Combine like terms: -4 + 4 = 0 0 + x = 2.828427125 + 4 x = 2.828427125 + 4 Combine like terms: 2.828427125 + 4 = 6.828427125 x = 6.828427125 Simplifying x = 6.828427125

Subproblem 2

x + -4 = -2.828427125 Simplifying x + -4 = -2.828427125 Reorder the terms: -4 + x = -2.828427125 Solving -4 + x = -2.828427125 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + x = -2.828427125 + 4 Combine like terms: -4 + 4 = 0 0 + x = -2.828427125 + 4 x = -2.828427125 + 4 Combine like terms: -2.828427125 + 4 = 1.171572875 x = 1.171572875 Simplifying x = 1.171572875

Solution

The solution to the problem is based on the solutions from the subproblems. x = {6.828427125, 1.171572875}

See similar equations:

| 2n^3-24n^2-23048n=0 | | 4.3+7.5=5.8 | | 10v^2=11v+6 | | -3-10=-46 | | -(12+2r)-(r+8)=-7r+3r | | 10U-2U= | | 6x^2-13x+4= | | 4.29b-0.692=11.749 | | 3[2(5x-7)-3(4x-6)]-4[5(x-1)-7x]=6[-4(x+2)+7x] | | 6+5(8w-9)= | | 36=2L+W | | 1w+5=4 | | 3-2(x-4)=2x-5 | | 3(4x+1)=3+12x-2 | | (X+10)+(4x-20)=90 | | 7R*2+8R+8R= | | 3x(.29)=3 | | 1y+-4x= | | 8v-18=26+3v | | 18+4(-4)= | | 50-40x=200 | | 3t-t=20 | | X^5-2x^4+x^3-x^2+2x-1=0 | | 50+40x=200 | | 5a-2b=8displayngb | | 7+3k-4k=-5-3k | | -5g+1=7+2a | | 2n^3-24n^2-23048=0 | | 2y-4=10x | | 7T+8(7T+2)= | | 4(k+5)=2(9k-2) | | 24xy+6y=0 |

Equations solver categories